Genome-wide identification and characterization of tissue-specific non-coding RNAs in black pepper (Piper nigrum L.) - Kumar, Baibhav; Saha, Bibek; Jaiswal, Sarika; Angadi, U. B.; Rai, Anil; Iquebal, Mir Asif (Frontiers in Plant Science, 2023)
Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) are the two classes of non-coding RNAs (ncRNAs) present predominantly in plant cells and have various gene regulatory functions at pre and post-transcriptional levels. Previously deemed as “junk”, these ncRNAs have now been reported to be an important player in gene expression regulation, especially in stress conditions in many plant species. Black pepper, scientifically known as Piper nigrum L., despite being one of the most economically important spice crops, lacks studies related to these ncRNAs. From a panel of 53 RNA-Seq datasets of black pepper from 6 tissues, namely, flower, fruit, leaf, panicle, root and stem of 6 black pepper cultivars, covering 8 bioprojects across 4 countries, we identified and characterized a total of 6406 lncRNAs. Further downstream analysis inferred that these lncRNAs regulated 781 black pepper genes/ gene products via miRNA-lncRNA-mRNA network interactions, thus working as ceRNAs. The interactions may be various mechanisms like miRNA-mediated gene silencing or lncRNAs acting as endogenous target mimics (eTMs) of the miRNAs. A total of 35 lncRNAs were also identified to be potential precursors of 94 miRNAs after being acted upon by endonucleases like Drosha and Dicer. Tissue-wise transcriptome analysis revealed 4621 circRNAs. Further, miRNA-circRNA-mRNA network analysis showed 432 circRNAs combining with 619 miRNAs and competing for the binding sites on 744 mRNAs in different black pepper tissues. These findings can help researchers to get a better insight to the yield regulation and responses to stress in black pepper in endeavor of higher production and improved breeding programs in black pepper varieties.